Psychiatrists, Penguins and Pelicans: media psychiatrists and psychiatrists in the media - Gavin Miller; Gordon David Lyle Bates (BJPsych Bulletin)
To provide a useful contextual backdrop to an exhibition at the Royal College of Psychiatrists this summer, we used a question and answer format to summarise the thoughts of its curator, Gavin Miller. Gavin has chosen 12 books published by Penguin between 1949 and 1975 to illuminate the relationship between psychiatrists, psychologists, psychotherapists and the British media. He reflects on the opportunities and pitfalls that come with the association, the motivations of previous writers and provides practical advice for any media psychiatrists considering such a role in the future. The exhibition is open to visitors to the College building in London.